The Effect of Reducing the "Jumping to Conclusions" Bias on Treatment Decision-Making Capacity in Psychosis: A Randomized Controlled Trial With Mediation Analysis. (26th September 2018) - Turner, David T; MacBeth, Angus; Larkin, Amanda; Moritz, Steffen; Livingstone, Karen; Campbell, Alison; Hutton, Paul
Abstract: Background: Evidence-based psychological interventions to support treatment decision-making capacity (capacity) in psychosis do not currently exist. This study sought to establish whether reducing the extent to which this group form conclusions based on limited evidence, also known as the "jumping-to-conclusions" (JTC) bias, could improve capacity. Methods: In a randomized controlled open trial, 37 patients aged 16–65 years diagnosed with schizophrenia-spectrum disorders were randomly assigned (1:1) to receive a single-session intervention designed to reduce the JTC bias (MCT-JTC; adapted from Metacognitive Training [MCT]) or an attention control (AC) condition designed to control for therapist attention, duration, modality, and face validity. Primary outcomes were treatment decision-making capacity measured by the MacArthur Competency Assessment Tool for Treatment (MacCAT-T) and the jumping-to-conclusions reasoning bias measured by draws to decision on the beads task, each of which were administered by the psychologist delivering the intervention. Results: Those receiving MCT-JTC had large improvements in overall capacity ( d = 0.96, P < .05) and appreciation ( d = 0.87, P < .05) compared to those receiving AC. Reduction in JTC mediated a large proportion of the effect of group allocation on understanding, appreciation, reasoning, and overall MacCAT-T scores. Conclusion: This is the first experimental investigation of the effect of a psychological intervention on treatment decision-making capacity in psychosis. It provides early evidence that reducing the JTC bias is associated with large and rapid improvements in capacity. Due to limited resources, assessments were administered by the researchers delivering the intervention. Results should therefore be considered preliminary and a larger, definitive trial addressing methodological limitations is warranted.